Granulysin species segregate to different lysosome-related effector vesicles (LREV) and get mobilized by either classical or non-classical degranulation. (March 2019) - Lettau, Marcus; Dietz, Michelle; Dohmen, Katharina; Leippe, Matthias; Kabelitz, Dieter; Janssen, Ottmar
Highlights: In lymphocytes 9 kDa and 15 kDa granulysin segregate to different storage granules. 9 kDa and 15 kDa granulysin are differentially released from lymphocytes. Calcium-independent non-classical degranulation governs release of 15 kDa granulysin. 9 kDa granulysin mobilization employs classical calcium-dependent degranulation. Abstract: Granulysin (GNLY) is a cationic antimicrobial, proinflammatory, and cytotoxic effector protein primarily expressed in human cytotoxic T and NK cells. Its two variants, the 15 kDa precursor and the mature 9 kDa protein processed by proteolysis, act on different microbes or infected and transformed target cells and utilize mechanistically different effector activities. In human peripheral blood lymphocytes of healthy individuals, both forms of GNLY are detected in TCR αβ + (CD4 + and CD8 + ) T cells, TCR γδ + T cells, and CD3 − CD56 + NK cells. In general, classical cytotoxic cells (i.e. CD8 + TCR αβ + T cells, TCR γδ + T cells, and NK cells) contain effector proteins in higher abundance in more cells of the subset as compared to TCR αβ + CD4 + T cells. Imaging flow cytometry analyses demonstrate that the subcellular localization and internal pools of 9 kDa and 15 kDa GNLY are virtually non-overlapping. The 9 kDa form is enriched in dense granules that also contain granzymes (Grz) and carry CD107a, whereas 15 kDa GNLY is associated with CD107a-negative lysosome-related effector vesicles. We further demonstrate that 15 kDa GNLY serves as an additional indicator for non-classical, PKC-dependent degranulation while the liberation of granules containing 9 kDa GNLY requires calcium mobilization. Our studies provide a deeper insight into the subcellular localization and release mechanisms of the individual GNLY species. This information will not only be useful for the interpretation of GNLY-related pathophysiologies, but also for the development of therapeutic interventions employing distinct GNLY effector functions for microbial targeting or immunoregulation.